Topology restoration algorithm for heterogeneous sensor networks based on connected dominating tree - Ting-jun SHI; Xu-ming FANG; Yun YANG (Tongxin xuebao)
For currently lacking the study of the topology restoration algorithm for heterogeneous sensor networks,a topology restoration algorithm for heterogeneous sensor networks based on connected dominating tree (HSNTR) was proposed.Firstly the algorithm constructed a virtual backbone forwarding data at very low cost,and secondly when a node fails,the algorithm would dynamically locally restore the backbone to make it still connect and cover all nodes.Theoretical analysis proved the maximum number of nodes the algorithm uses during constructing and restoring the backbone.Simulation analysis showed that the algorithm is better than other algorithms in terms of energy efficiency,scalability and reliability.